PERANCANGAN ALAT BENCH TEST DENGAN 5 VALVE UJI CLASS 800 UNTUK SATU SIKLUS - Dionisius, Felix; Annabani , Muhammad Taqiyyudin; Suhardi, Suhardi; Chaerul, Chaerul (Jurnal Rekayasa Mesin, 2024)
Hydrotest testing carried out in the valve industry still uses manual methods. This makes the hydro test process less efficient in processing time. Therefore, it is necessary to design a valve testing tool to speed up the testing process. The tool is designed must be able to withstand the hydro test pressure in the specified number of valves simultaneously. This research was a design on frame strength testing which aims to operate at certain pressures by standards. The method was used by numerical simulation and theoretical. Theoretical with cross or distribution method was used as validation of numerical simulation results. The results of the numerical simulation show safe results when operating with a von misses stress of 193,155 N/mm2. While the error of the design produced with theoretical calculations is 32-33%.